2002
DOI: 10.1212/wnl.59.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Anti–basal ganglia antibodies in acute and persistent Sydenham’s chorea

Abstract: These results support the hypothesis that Syndenham's chorea is an autoantibody-mediated disorder. Western immunoblotting and immunofluorescence are the best methods for detecting anti-basal ganglia antibodies, and reactivity to basal ganglia antigens of 40, 45, and 60 kDa were commonly seen in both acute and persistent cases of SC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
172
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(193 citation statements)
references
References 14 publications
13
172
1
5
Order By: Relevance
“…TS patient sera have previously been shown to detect several protein species including a 60 kDa protein in immunoblots of human postmortem brain tissue lysates (Church et al, 2003;Singer et al, 1998;Wendlandt et al, 2001). A 60 kDa protein was similarly recognized by Sydenham's chorea patients' sera (Church et al, 2002) and recently identified as PK (Dale et al, 2006). Antibodies to PK were the most predominant of three glycolytic proteins identified as antigenic targets in the sera of patients with Sydenham's chorea.…”
Section: Discussionmentioning
confidence: 92%
“…TS patient sera have previously been shown to detect several protein species including a 60 kDa protein in immunoblots of human postmortem brain tissue lysates (Church et al, 2003;Singer et al, 1998;Wendlandt et al, 2001). A 60 kDa protein was similarly recognized by Sydenham's chorea patients' sera (Church et al, 2002) and recently identified as PK (Dale et al, 2006). Antibodies to PK were the most predominant of three glycolytic proteins identified as antigenic targets in the sera of patients with Sydenham's chorea.…”
Section: Discussionmentioning
confidence: 92%
“…Further studies using immunofluorescence demonstrated antineuronal antibodies in 100% of acute SC although only 63% in persistent/chronic SC. 79,80 A further separate study also supported antibody reactivity in acute SC. 81 Church expanded on these findings using a different antibody technique (Western blotting) and proposed a restricted group of brain autoantigens of molecular mass 40, 45, and 60 kilodaltons (kDa) were involved in antibody binding.…”
Section: Anti-neuronal Antibodiesmentioning
confidence: 78%
“…1 We describe a boy who presented a mild parkinsonism and who after stopping corticoids had a dramatic evolution to an akinetic-mutism state associated with an inflammatory CSF and widespread brain lesions. Although ds-DNA was mildly positive, the diagnosis of systemic lupus erythematosus was considered less probable inasmuch as the antinuclear and anti-ENA antibodies were negative, complement levels were normal and no other clinical or laboratorial criteria was present.…”
Section: Introductionmentioning
confidence: 96%